Evaluation of Varicocele Frequency in Adolescents in the City of Isfahan - Homayoun Abbasi (International Journal of Fertility and Sterility, 2007)
Background Although varicocele can be treated, it is considered as one of the most common causes of infertility. This study was performed in order to estimate prevalence of varicocele in adolescents aging 12-14 years in the city of Isfahan.